Nano-Physical Characterization of Chemical Vapor Deposition-Grown Monolayer Graphene for High Performance Electrode: Raman, Surface-Enhanced Raman Spectroscopy, and Electrostatic Force Microscopy Studies - Won-Hwa Park (MDPI AG, 2021)
To achieve high-quality chemical vapor deposition of monolayer graphene electrodes (CVD-MG), appropriate characterization at each fabrication step is essential. In this article, (1) Raman spectroscopy/microscopy are employed to unravel the contact effect between the CVD-MG and Cu foil in suspended/supported formation. (2) The Surface-Enhanced Raman spectroscopy (SERS) system is described, unveiling the presence of a z-directional radial breathing-like mode (RBLM) around 150 cm−1, which matches the Raman shift of the radial breathing mode (RBM) from single-walled carbon nanotubes (SWCNTs) around 150 cm−1. This result indicates the CVD-MG located between the Au NPs and Au film is not flat but comprises heterogeneous protrusions of some domains along the z-axis. Consequently, the degree of carrier mobility can be influenced, as the protruding domains result in lower carrier mobility due to flexural phonon–electron scattering. A strongly enhanced G-peak domain, ascribed to the presence of scrolled graphene nanoribbons (sGNRs), was observed, and there remains the possibility for the fabrication of sGNRs as sources of open bandgap devices. (3) Electrostatic force microscopy (EFM) is used for the measurement of surface charge distribution of graphene at the nanoscale and is crucial in substantiating the electrical performance of CVD-MG, which was influenced by the surface structure of the Cu foil. The ripple (RP) structures were determined using EFM correlated with Raman spectroscopy, exhibiting a higher tapping amplitude which was observed with structurally stable and hydrophobic RPs with a threading type than surrounding RPs. (4) To reduce the RP density and height, a plausible fabrication could be developed that controls the electrical properties of the CVD-MG by tuning the cooling rate.